The concept of person between bioethics and biolaw. - Palazzani, Laura (Medicina e Morale, 2004)
The article argues about the concept of person, underlining the central role of this notion in bioethical issues in the last years. Really, the ways of interpretation the concept are various. In the context of actual debate, it is possible to recognise two opposite orientations to conceive the person. On the one hand, we have the "reductionist" vision (the human being is not always person; indeed, sometimes person is also the not human being); on the other hand, the "personalist" one (that support the identity among person and human being). The Author stops on the critical analysis of reductionist orientation, in its turn constituted by different bioethical and biojuridical theories, concluding that the notion of person - that was philosophically elaborated to characterise the human being - risks to be used against man himself, creating dangerous forms of "discrimination". The articles concludes with some reflections that support the theoretical choice to recognise an intrinsic dignity (ethics) and strong rights (law) to every human being, who have a personal statute from the conception until his death. In this way, a bio-law "for" the man is called to not be "neutral", but to take sides in favour of the protection and guardianship of the human being in all the circumstances, also when he is not able to claim his rights (e.g.: embryo and patient in persistent vegetative state).